Branding tourism and collaborative governance: A case study from Nglanggeran village - Mohamad Sukarno; Dyah Mutiarin (Jurnal Studi Komunikasi, 2023)
Nglanggeran Village has been recognised as a smart tourism destination and earned the "Best Tourism Village" title from the World Tourism Organization (UNWTO). This study delves into the analysis of collaborative governance within Nglanggeran Village, which has earned this esteemed recognition and explores tourism branding development through cross-sector efforts. Employing a qualitative research method with a case study approach focused on Nglanggeran Village, this research draws data from multiple sources, including mass media (10 sources related to the tourism branding of Nglanggeran Village) and the village's Twitter account. Data analysis is conducted using Computer-Assisted Data Analysis Software (CAQDS). The study applies branding theory, considering the following indicators: Product, Price, Place, and Promotion. The findings reveal that Nglanggeran Tourism Village's collaborative governance efforts have been fostered by the Tourism Awareness Group (Pokdarwis), which has forged partnerships with the Regional Government of Gunungkidul Regency, Special Region of Yogyakarta, and the Ministry of Tourism and Creative Economy. These collaborations involve mentoring and training to enhance tourism governance, focusing on aspects of natural, cultural, and educational tourism. Regarding tourism branding, mass media is pivotal in disseminating information about key tourism offerings, location coverage, and facilitating online ticket purchases. Furthermore, the @GunungApiPurba social media account collaborates with government entities to promote natural tourism, lodging packages, and various local food products, positioning itself as the central hub for branding while providing valuable information on access to the destination.